From Global Norms to Local Contestation: Explaining the Failure of Sustainable Aquaculture Governance in Bangladesh - Arie Raditya (International Journal Labs, 2026)
The rapid expansion of aquaculture has positioned sustainable aquaculture governance as a critical component of global environmental governance, particularly in addressing food security, economic development, and marine ecosystem protection. However, the implementation of sustainability principles in developing countries often produces uneven outcomes due to complex interactions between international norms, domestic institutions, and local political-economic conditions. This study aims to examine how global sustainable aquaculture norms are translated, adapted, and contested within Bangladesh’s shrimp aquaculture governance system. This research employed a qualitative case study approach using document analysis of peer-reviewed articles, policy documents, and reports from international organizations. The analytical framework integrates Acharya’s concept of Norm Localization with Political Ecology to explain the relationship between global governance agendas and local implementation processes. The findings indicate that sustainable aquaculture governance in Bangladesh has not failed solely because of institutional limitations or weak policy enforcement, but because international sustainability norms undergo selective adaptation within domestic political and economic structures. The results demonstrate that sustainability initiatives often prioritize export competitiveness and market compliance while generating unequal impacts among coastal communities, particularly small-scale producers. This study concludes that effective sustainable aquaculture governance requires a more inclusive approach that integrates environmental objectives with social justice, local participation, and equitable resource management. The findings contribute to broader discussions on environmental governance in the Global South.